An efficient transformation method for genome editing of elite bread wheat cultivars - Biswal, Akshaya K.; Hernandez, L. Ruben B.; Castillo, Ana I. R.; Debernardi, Juan M.; Dhugga, Kanwarpal S. (Frontiers in Plant Science, 2023)
An efficient genetic transformation protocol is necessary to edit genes for trait improvement directly in elite lines. We used a protein fusion between a wheat growth-regulating factor 4 (GRF4) and its interacting factor (GIF1) to develop a reproducible genetic transformation and regeneration protocol, which we then used to successfully transform elite bread wheat cultivars Baj, Kachu, Morocco, Reedling, RL6077, and Sujata in addition to the experimental cultivar Fielder. Immature embryos were transformed with the vector using particle bombardment method. Transformation frequency increased nearly 60-fold with the GRF4-GIF1-containing vectors as compared to the control vector and ranged from ~5% in the cultivar Kachu to 13% in the cultivar RL6077. We then edited two genes that confer resistance against leaf rust and powdery mildew directly in the aforementioned elite cultivars. A wheat promoter, TaU3 or TaU6, to drive the expression of guideRNA was effective in gene editing whereas the OsU3 promoter failed to generate any edits. Editing efficiency was nearly perfect with the wheat promoters. Our protocol has made it possible to edit genes directly in elite wheat cultivars and would be useful for gene editing in other wheat varieties, which have been recalcitrant to transformation thus far.